Long-Term Results of Rapid Maxillary Expansion and Facemask: Long-Term of Regular Protraction - Şirin Nevzatoğu; Nazan Küçükkeleş (Galenos Yayinevi, 2014)
Objective:Evaluation of the long-term skeletal, dental, and soft tissue treatment results of 17 patients who completed their protraction with the facemask.Materials and Method:Twenty-three Class III patients with a mean age of 12, characterized with maxillary retrognathism, who were treated by facemask protraction therapy, were recalled after 6.08 years following protraction. Only 17 patients presented and their records were renewed. Study was carried out on the initial (T0), after protraction (T1), and 6.08 years following protraction (T2) films. Long-term skeletal, dental, and soft tissue changes were measured.Results:After 6.08 years, the profile and dental relationships achieved by protraction were found to be well maintained clinically. The cephalometric examination revealed stable sagittal advancement with a mandibular forward positioning. After protraction (T1) and at 6.08 years of recall (T2), there were no statistically significant changes found in parameters showing sagittal position of the maxilla (SNA, maxillary depth, and NperA). On the other hand, in the long term, statistically significant increase was noted in the SNB angle, indicating late mandibular growth. In the long term, although the forward positioning of the mandible took place, there was no dental relapse seen, probably because of the significant upper incisor proclination (SN-UI [T1]: 100.05°; [T2]: 111.26°), which indicates the dental camouflage.Conclusion:Advancement achieved by the facemask was found to be stable in the long term. The most important point at which the clinician must pay attention is the late mandibular growth.